Comparative Politics with Intraparty Candidate Selection - Benoit S.Y. Crutzen; Nicolas Sahuguet (Tinbergen Institute, 2022)
Politicians respond to incentives when they decide how to allocate their campaigning time and effort. The literature suggests electoral rules impact politicians' incentives. We argue that the candidate selection process is an equally important source of incentives. We develop a two-stage model in which parties select candidates before the election. Elections are under first past the post (FPTP) or closed list proportional representation (PR). Selection is competitive or non-competitive. When selection is not competitive, effort is higher under FPTP. With competitive selection, effort is higher under PR as, under PR, competition motivates candidates to exert effort to be selected(as under FPTP) and to be ranked higher on the list. The results point to a causal relationship between electoral rules and how parties porganize. They suggest empirical studies comparing electoral rules should consider how parties organize.
Keywords: 330; electoral rule; candidate selection process; moral hazard